2021
DOI: 10.3389/fbioe.2021.745099
|View full text |Cite
|
Sign up to set email alerts
|

Streptomycin Sulfate–Loaded Niosomes Enables Increased Antimicrobial and Anti-Biofilm Activities

Abstract: One of the antibiotics used to treat infections is streptomycin sulfate that inhibits both Gram-negative and -positive bacteria. Nanoparticles are suitable carriers for the direct delivery and release of drug agents to infected locations. Niosomes are one of the new drug delivery systems that have received much attention today due to their excellent biofilm penetration property and controlled release. In this study, niosomes containing streptomycin sulfate were prepared by using the thin layer hydration method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 68 publications
1
23
0
Order By: Relevance
“…Mansouri et al studied the antimicrobial effects of niosomes loaded streptomycin against some pathogenic strains. The results of this study showed that niosomes containing streptomycin can reduce MIC value by 4-8 times, which indicated the significant effects of niosomes containing streptomycin 43 . Hedayati et al encapsulated tobramycin in niosomes and studied its antimicrobial effects against Pseudomonas aeruginosa strains.…”
Section: Antimicrobial Activitymentioning
confidence: 59%
“…Mansouri et al studied the antimicrobial effects of niosomes loaded streptomycin against some pathogenic strains. The results of this study showed that niosomes containing streptomycin can reduce MIC value by 4-8 times, which indicated the significant effects of niosomes containing streptomycin 43 . Hedayati et al encapsulated tobramycin in niosomes and studied its antimicrobial effects against Pseudomonas aeruginosa strains.…”
Section: Antimicrobial Activitymentioning
confidence: 59%
“…Previous researchers have reported on the same trend [ 33 , 34 , 35 ]. As the surfactant chain length extends, drug release can last longer because the transfer temperature can influence the surfactants and make them totally fluid, allowing for increased drug penetration at 37 °C [ 2 ]. In general, the in vitro release profile showed sustained release of medicines from the niosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Novel drug delivery systems have the advantage of delivering drug molecules to sites of action thereby eliciting optimal response. They can act as drug reservoirs, modify drug release and help to minimize adverse effects of drugs by reducing off-target activity [ 1 , 2 , 3 ]. Oral route is the most preferred route for administration of therapeutic agents because of the ease of handling and patient compliance to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[4] MDR pathogenic bacteria use alternative strategies to become resistant to different classes of antimicrobial agents, one of which is biofilm production. [5] Biofilms are a community of bacterial cells surrounded by an extracellular matrix that can adhere tightly to medical surfaces and prevent antibiotics from entering microbial cells. [6] In addition, biofilms also play an important role in pathogenesis via immune system escape and inhibition of drug entry into microbial cells.…”
Section: Introductionmentioning
confidence: 99%